2019
DOI: 10.3389/fmicb.2019.00938
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Control of Manganese Doping in Zinc Sulfide Nanomaterial Using Shewanella oneidensis MR-1

Abstract: Bacteria naturally alter the redox state of many compounds and perform atom-by-atom nanomaterial synthesis to create many inorganic materials. Recent advancements in synthetic biology have spurred interest in using biological systems to manufacture nanomaterials, implementing biological strategies to specify the nanomaterial characteristics such as size, shape, and optical properties. Here, we combine the natural synthetic capabilities of microbes with engineered genetic control circuits toward biogenically sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…In the case of C. freundii mostly extracellular clusters of CdS nanoparticles were observed around of the cells (Figure 2 E/F). The CdS nanoparticles formed by S. oneidensis appeared as smaller spherical spots uniformly distributed on the cell surface (Figure 2 I/H), in agreement with previous studies [41, 42] . In the case of E. coli , small clusters of CdS particles were observed on the cell surface (Figure 2 K/L).…”
Section: Resultssupporting
confidence: 90%
“…In the case of C. freundii mostly extracellular clusters of CdS nanoparticles were observed around of the cells (Figure 2 E/F). The CdS nanoparticles formed by S. oneidensis appeared as smaller spherical spots uniformly distributed on the cell surface (Figure 2 I/H), in agreement with previous studies [41, 42] . In the case of E. coli , small clusters of CdS particles were observed on the cell surface (Figure 2 K/L).…”
Section: Resultssupporting
confidence: 90%
“…TheC dS nanoparticles formed by S. oneidensis appeared as smaller spherical spots uniformly distributed on the cell surface (Figure 2I/H), in agreement with previous studies. [41,42] In the case of E. coli,s mall clusters of CdS particles were observed on the cell surface (Figure 2K/L). Theb iohybrid systems were further characterized by X-ray powder diffraction (XRD,F igure 3).…”
Section: Characterization Of the Biohybrid Systemsmentioning
confidence: 94%
“…Recently, Chellamuthu et al developed a genetic-control strategy to biosynthesize manganese-doped ZnS (Mn:ZnS) nanoparticles with different doping levels (Fig. 5 ) [ 155 ]. The authors found that the Mn doping level changed as a function of added inducer when the engineered strain of S. oneidensis with inducible expression of MtrCAB complex was used to control the reduction of Mn 4+ oxide.…”
Section: Biosynthesis Of Metal Nanoparticlesmentioning
confidence: 99%
“…5 Controlling manganese doping of ZnS quantum dots by engineered S. oneidensis JG3631 with the inducible expression of MtrCAB complex. a Chemically synthesized Mn doped ZnS NPs with varying optical properties, b the amount of the inducer (TMAO) regulating expression of MtrCAB complex that performs extracellular reduction, c relationship between Mn 2+ concentration and the addition of TMAO, d biogenic Mn doped ZnS quantum dots with varying optical properties as a function of Mn 2+ concentration [ 155 ]. …”
Section: Biosynthesis Of Metal Nanoparticlesmentioning
confidence: 99%